Evaluation of Dynamic Compressive Properties of Pla/Pbat Polymer Alloys Using Split Hopkinson Pressure Bar Method - NISHIDA, M.; ICHIHARA, H.; FUKUDA, N. (Engineering Transactions, 2011)
Poly(lactic acid) (PLA) is a biodegradable biomass polymer. Polymer blends or polymer alloys have been used to overcome its brittleness. Because poly(butylene/adipate/terephthalate) (PBAT) is a ductile and biodegradable polymer, PLA/PBAT polymer alloys can potentially exhibit high impact strengths. Different mixing ratios of PLA/PBAT (80:20, 70:30 and 60:40) and the addition of dialkylperoxide as compatibilizing agent for each mixing ratio have been examined. The stress-strain curves of the PLA/PBAT specimens (observed using a scanning electron microscope) were measured using a split Hopkinson pressure bar (Kolsky bar) and a universal testing machine. The PBAT ratios and addition of dialkylperoxide affected the stress-strain curves. Yield stress decreased with increasing PBAT ratios. Addition of dialkylperoxide did not change the yield stress of specimens when PLA:PBAT = 80:20. At high strain rates, the addition of dialkylperoxide clearly reduced yield stress and Young’s modulus when PLA: PBAT = 70:30 and 60:40.